Mortality of the Atlantic ghost crab Ocypode quadrata (Fabricius, 1787) due to vehicle traffic on sandy beaches: A road ecology approach. (15th April 2020) - Costa, Leonardo Lopes; Secco, Helio; Arueira, Vitor Figueira; Zalmon, Ilana Rosental
Abstract: Sandy beaches are not roads, but they have been used as such worldwide, threatening endemic fauna such as ghost crabs (Crustacea: Ocypodidae). The objective of the present study was to identify the spatial factors influencing the incidence of ghost crabs ( Ocypode quadrata ) killed by vehicles. This study included a systematic study of carcasses with clear signals of crushing by cars on beaches with distinct urbanization levels and on dirt roads crossing low-urbanized beach stretches. Predictive variables (e.g., tyre tracks on the sand, proxies of urbanization, distance from coastal lagoons and beach width) were obtained for the kill points and random points. Generalized linear models with binomial distributions showed that the number of tyre tracks nearby (positive correlation) and indicators of urbanization in the environment (negative correlation) were the main variables explaining ghost crab kills on the beach. Similarly, the likelihood of finding crabs killed by vehicles on the dirt road was associated with the areas with the densest ghost crab populations (higher beach width and low-urbanized areas). Therefore, as an important conservation strategy and mitigation action, vehicle traffic must be severely controlled mainly on low-urbanized beaches, both on the sand and dirt roads crossing natural beach vegetation. Highlights: We applied the road ecology approach to investigate vehicle-ghost-crab collisions. Ghost crabs killed by vehicles were found on the beach and on the dirt road. Ghost crabs deaths were related with higher vehicle traffic and lower urbanization. Surveillance of beach driving is essential for coastal biodiversity conservation.